Comparison and combined use of NEWS2 and GCS scores in predicting mortality in stroke and traumatic brain injury: a multicenter retrospective study - Hu, Wei; Shang, Ke; Chen, Liqin; Wang, Xin; Li, Xia (Frontiers in Neurology, 2024)
Objective: This study aims to assess the effectiveness of the National Early Warning Score 2 (NEWS2) versus Glasgow Coma Scale (GCS) in predicting hospital mortality among patients with stroke and traumatic brain injury (TBI). Location: This multicenter study was conducted at two anonymized tertiary care hospitals in distinct climatic regions of China, with a combined annual emergency admission exceeding 10,000 patients. Patients: The study included 2276 adult emergency admissions diagnosed with stroke (n=1088) or TBI (n=1188) from January 2021 to December 2023, excluding those with chronic pulmonary disease, severe cardiac conditions, or a history of brain surgery Measuring and Main Outcomes: The receiver operating characteristic (ROC) curve and the area under the curve (AUC) were utilized to analyze the predictive accuracy of NEWS2 and GCS for hospital mortality at 24, 48, and 72 hours postadmission and at discharge. Results: Out of 2276 patients (mean age 61.4, 65.6% male), 1855 survived while 421 succumbed. NEWS2 demonstrated superior predictive accuracy (AUC = 0.962) over GCS (AUC = 0.854) for overall hospital mortality. Specifically, NEWS2outperformed GCS in predicting mortality at 24 hours (0.917 vs 0.843), 48 hours (0.893 vs 0.803), and 72 hours (0.902 vs 0.763). Notably, despite a higher AUC for NEWS2 at predicting 24-hour hospital mortality, the sensitivity and specificity of GCS were considerably lower (12% and 31%, respectively) compared to NEWS2 (sensitivity of 95% and specificity of 81%).Subgroup analysis showed NEWS2 outperforming GCS in predicting inhospital mortality for TBI and stroke patients. For TBI patients (n=260), NEWS2 had an AUC of 0.960 (95% CI: 0.948-0.973) vs. GCS's AUC of 0.811 (95% CI: 0.781-0.840). For stroke patients (n=161), NEWS2 had an AUC of 0.930 (95% CI: 0.908-0.952) vs. GCS's AUC of 0.858 (95% CI: 0.823-0.892). NEWS2 showed greater sensitivity in both groups, highlighting its effectiveness in identifying high-risk neurological patients.Conclusion: NEWS2 scores are more precise and effective in predicting hospital mortality in stroke and TBI patients compared to GCS scores, although slightly less so within the first 24 hours. Combining NEWS2 with GCS and clinical findings within the initial 24 hours is recommended for a comprehensive prognosis evaluation.